PERSEPSI MAHASISWA PGSD ANGKATAN 2024 UNDANA TERHADAP PENGGUNAAN AI DALAM PROSES BELAJAR MANDIRI - Bernadus, Berthi Christiani; Veridiana Wuleng, Maria; Arianto Tanesab, Rony; Melani Lodika Natonis, Sania; Else Abineno, Gradiana; Jati Lamauran Koten, Gaudensius; Wonda, Hiwa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of Artificial Intelligence (AI) technology has brought significant changes to the field of education, particularly in supporting students’ self-directed learning processes. However, the increasing use of AI has also generated various perceptions, both positive and negative, especially regarding learning effectiveness, independence, and the potential for technological dependency. This study aims to investigate the perceptions of the 2024 cohort students of the Primary School Teacher Education Program (PGSD) at Nusa Cendana University toward the use of AI in self-directed learning. The research employs a descriptive approach using a survey method. The population consists of all PGSD students from the 2024 cohort at Nusa Cendana University, while the sample is selected through purposive sampling, focusing on students who actively utilize AI in their learning activities. Data are collected through questionnaires based on a Likert scale and documentation techniques. The data are analyzed using descriptive statistics with the assistance of IBM SPSS Statistics software. The aspects examined include the ease of AI use, the benefits of AI in learning, the effectiveness of AI utilization, its impact on self-directed learning, the level of dependency on AI, and students’ attitudes toward AI usage. The findings are expected to provide an overview of how students perceive AI as a tool to support self-directed learning and serve as a reference for lecturers and the study program in developing learning strategies that are adaptive to technological advancements. Furthermore, this study is expected to contribute to the development of digital literacy and the responsible use of AI in higher education.